Hepatitis B Testing: Old Tricks for Newborn Players. Issue 6 (June 2020) - Azhar, Zainul; Purcell, Rachael; Buttery, Jim; Doherty, Richard
Abstract : We describe 2 preterm neonates with transient hepatitis B surface (HBs) antigenemia detected after Hepatitis B vaccination. Repeat serology in both cases tested negative for hepatitis B surface antigen, confirming transient HBs antigenemia. The duration of transient HBs antigenemia affirms current literature in the pediatric population.